THE INFLUENCE OF CYBERLOAFING, LOCUS OF CONTROL AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN UNIVERSITY EDUCATIONAL PERSONNEL 17 AUGUST 1945 BANYUWANGI - Mohamad Irfan; Wardha Nilawati; Mohammad Fahrurrozi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine the effect of cyberloafing, locus of control and work discipline on employee performance. The population and sample of this research is research on educational staff at the University of 17 August 1945 Banyuwangi, totaling 63 respondents. The method used in this research uses quantitative methods, sampling techniques using non-probability sampling techniques, namely saturated samples (census). Data analysis takes the form of outlier test, validity test, reliability test, classical assumption test, multiple linear regression analysis, determination test (R2), and hypothesis testing. The results of this research are that the F count > F table test results are 4.224 > 2.811, and the sig value is 0.010 < 0.05, so it can be concluded that the influence of Cyberloafing, Locus of control and Work Discipline simultaneously influence the dependent variable, namely employee performance. The Adjusted R Square value is 0.168 or 1.68%, meaning that employee performance is influenced by cyberloafing, locus of control and work discipline, while the remaining 82.3% of employee performance is influenced by other variables that are not known in this research.